Semantics of immersive web through its architectural structure and graphic primitives - Bolivar, Holman; Pacheco, Alexander; González-Crespo, Rubén (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
Currently, practices and tools for computer-aided three-dimensional design, do not allow the semantic description of objects constructed in some cases specified notations as handling layers, or labeling of each development itself. The lack of a standard for the description of the elements represents a major drawback for using advanced three-dimensional environments such as the automation of search and construction processes that require semantic knowledge of its elements. This project proposes the development the semantic composition from the hierarchy of three-dimensional visualization of graphics primitives used to construct three-dimensional objects, taking into account the geometric composition architecture of standard 19775-1 of the International Electrotechnical Commission of the International Organization for Standardization For the development of semantic composition use the methodology methontology proposed by the Universidad Politécnica de Madrid, because it allows the construction of ontologies about specific domains, limiting the domain by defining classes and subclasses, relationships and the generation of instances a framework for resource description on web ontology language.
Keywords: computer aided design; geometry; artificial intelligence; IJIMAI